MIP Improves Detection of Brain Metastases. Issue 6 (November 2016) - Sepulveda, Francisco; Yáñez, Paulina; Carnevale, Martin Diego; Romero, Carlos; Castillo, Mauricio
Abstract : Purpose: This study aimed to compare the sensitivity for detection of brain metastases using postcontrast 3-dimensional, T1W-gradient echo sequence (3DT1W) and maximum intensity projections (MIPs) obtained from the same data set. Materials and Methods: A prospective analysis of patients with known brain metastases was performed. We compared 1-mm postcontrast 3DT1W with 6-mm MIP reconstructions obtained from the same images (MIP-3DT1) in 95 patients using 1.5 (42 patients) and 3 T (53 patient). Two independent readers analyzed all studies and the examinations were presented in anonymized and random fashion for a total of 190 interpretations per observer. One reader had more than 20 years of experience and the second reader had 1 year of experience. Results: The least experienced observer found 542 brain metastases on postcontrast non-MIP 3DT1W and 605 with the MIP-3DT1 technique. For this observer, use of MIP resulted in increased number of detected metastases in 36% of patients regardless of field strength. The more experienced observer found 589 brain metastases on non-MIP 3DT1W and 621 with the MIP-3DT1 technique and the use of the latter also resulted in increased detection of metastases in 33% of patients regardless of field strength. Conclusions: In our study, we found that using MIP-3DT1 reconstructions of previously obtained postcontrast 3DT1W improved detection of brain metastases. This improvement was experienced by both the junior and experienced neuroradiologists and was also better at 3.0 T than at 1.5 T.